The Effectiveness of PAI Learning in Merdeka Curriculum to Overcome Student Stereotypes at SMAS Budi Agung Medan - Zega, Zaidan; Fadhila Daulay, Afrahul (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to explore the effectiveness of PAI learning in using the Merdeka Curriculum in overcoming student stereotypes. This research involves a scope of study that includes the implementation of Merdeka Curriculum in PAI learning and its impact on students' perceptions regarding existing stereotypes. The research method used is a case study by collecting data through observation, interviews and documentation with students and PAI teachers. The results showed that PAI learning with an independent curriculum can be effective in overcoming student stereotypes. The Independent Curriculum provides opportunities for students to develop a broader understanding of Islam, strengthen their identity as individual Muslims, and appreciate diversity in the school community. In addition, PAI learning with the Independent Curriculum also provides space for students to build harmonious relationships between fellow students and teachers, without reinforcing existing negative stereotypes.